AGRIBUSINESS DEVELOPMENT STRATEGY OF SOYBEAN COMMODITY IN SIGI REGENCY - Eru Rengga Patra; Lien Damayanti; Yulianti Kalaba (Tadulako University, 2016)
This research aimed to: 1) Knowing the strengths, weaknesses, opportunities and threats for agribusiness development of soybean commodity in Sigi Regency; 2) Knowing the right alternative strategy formula for the development of soybean commodity agribusiness in Sigi Regency; 3) Knowing the priority strategy that should be chosen for the agribusiness development of commodity soybean in Sigi Regency. This research purposively conducted in Sigi Regency from January to March 2017, and 6 respondents were chosen. SWOT analysis used to find alternative strategy, and QSPM analysis used to find priority strategy. The availability and productivity of the land is among the main strenghts, and the quality and quantity of human resources is among the main weaknesses.The main opportunity is the price of soybean commodity in the market, while imports of soybeans by the government is the main threats. The alternative and priority strategy that could be undertaken by the governmenr are : 1) Participatory motivation and farmers empowerment program; 2) Strengthening local soybean development policy that is pro-farmer; 3) Soybean cultivation development program through area expansion and land mapping; 4) Regional Agricultural Partnership; 5) Development of soybean processing industry.